Effectiveness of indoor plants vs. HEPA purifiers in the removal of PM2.5 and PM10 - Rukpakavong, Wilawan; Nilpanich, Sirikunya; Subsomboon, Kannikar (Edelweiss Applied Science and Technology, 2025)
Particulate matter (PM) is a major contributor to air pollution in many countries, including Thailand. The use of high-efficiency particulate air (HEPA) filters in air purifiers is currently the most common solution. However, in the context of PM removal, it is worth exploring how nature-based technologies could be employed to combat indoor air pollution and support the broader goals of urban sustainability. This study compares the efficiency of HEPA air purifiers with selected dust-collecting indoor plants. For a day, incense sticks were burned nonstop in two enclosed rooms with air purifiers and another with plants that reduce dust. PM2.5 and PM10 levels were monitored until the air quality met safety standards. The results indicated that plants with rough, hairy surfaces, bush-like shapes, and large leaf surface areas collected the most dust. Among the tested species, Boston Fern and Monstera demonstrated the highest air-cleaning efficiency per square meter of leaf area per hour. By contrast, in heavily polluted conditions (e.g., due to incense burning), it took the plants approximately 1.67–3.55 times longer for PM2.5 and 2.0–3.6 times longer for PM10 to reach safe levels compared to the air purifiers. These findings provide valuable insights for individuals deciding between air purifiers and indoor plants for improving indoor air quality.